Pengaruh Kepuasan Kerja Dan Semangat Kerja Terhadap Kinerja Karyawan Pada PT. Javadwipa Duta Mandiri Surabaya - Delsiana Susanti Ina Kii (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
This study aims to analyze and determine the effect of job satisfaction and morale on employee performance at PT Javadwipa Duta Mandiri Surabaya. This study took 45 respondents from a total population of 72 employees at PT Javadwipa Duta Madiri Surabaya where a total of 45 respondents all came from the marketing department. The analysis technique used is multiple linear regression analysis to test the hypothesis. While the classic assumptions used include the Normality Test, Multicollinearity Test, and Heteroscedasticity Test using the SPSS version 20 statistical program. The results of the analysis conclude that variables 1.) Job Satisfaction have no significant effect on Employee Performance, 2.) Work Morale have a significant effect on Employee Performance, 3.) Job Satisfaction and Work Morale have a simultaneous or joint effect on Employee Performance. at PT Javadwipa Duta Mandiri Surabaya.